The post-2015 Global Agenda – a role for local government (Commonwealth Journal of Local Governance, 2015)
Introduction:The Commonwealth Local Government Conference 2015 – Local Government 2030: Achieving the Vision is taking place at a crucial time of flux and change. The period of implementation for the Millennium Development Goals (MDGs) is drawing to a close, and the global community has been and indeed, still is, actively debating what should replace them. Local government is working hard to ensure that the post-2015 global development agenda reflects the important role of local government in defining, implementing and monitoring the new targets. It is a unique opportunity for local government to make its voice heard, to promote the importance of localisation in the debate, and to position local government as a key partner in the implementation of the proposed Sustainable Development Goals (SDGs).